Synthesis and Analysis of Ketoprofen 1,4-Sorbitan Ester - Pooreum Lim; Jae Ho Shim (Molbank)
This study presents the synthesis and comprehensive characterization of ketoprofen 1,4-sorbitan ester, a novel compound with potential applications in drug delivery. The compound was synthesized through a two-step process involving the acid-catalyzed dehydration of D-Glucose to form 1,4-sorbitan, followed by esterification with ketoprofen. The structures of ketoprofen 1,4-sorbitan ester and the reference compound, ketoprofen methyl ester, were rigorously analyzed using a combination of advanced analytical techniques. High-resolution accurate mass liquid chromatography–mass spectrometry was used to determine the precise molecular mass and elemental composition of the synthesized compounds. 1H and 13C nuclear magnetic resonance spectroscopy provided detailed information on the molecular structure and atomic connectivity to identify the specific functional groups and confirm the formation of ester bonds.